GROWTH PERFORMANCE OF BLACK NILE FISH (Oreochromis niloticus) WITH A COMBINATION OF COMMERCIAL FEED AND INDEPENDENT FEED AT THE P2MKP FISH BOSTER CENTER, BUNCITAN VILLAGE, SEDATI DISTRICT, SIDOARJO REGENCY, EAST JAVA PROVINCE - Prasojo, Muhammad Grafirahul; Fauziah, Anna; Cahyanurani, Annisa Bias (Jurnal Perikanan Unram, 2025)
The fisheries sector supports food security, one of which is through black tilapia cultivation which has many advantages. The study was conducted at the P2MKP Fish Boster Center to assess the effect of using a combination of commercial and independent feed on the growth of black tilapia, to find an alternative feed that is efficient, economical and supports optimal growth. The study was conducted at the P2MKP Fish Boster Center, Sidoarjo, using survey and internship methods. Activities include pond preparation, seed distribution, provision of a combination of commercial and independent feed, and monitoring the growth and health of black tilapia. Data were collected through observation, interviews and documentation and analyzed descriptively quantitatively. The water quality in the black tilapia pond was monitored well with a temperature of 28oC - 33oC, pH 8 and DO 4.3 - 4.62 ppm. Growth showed optimal results: SGR 1.29, absolute weight 198.75 grams, absolute length growth 20 cm, Survival Rate 85% and FCR 1.1. Commercial feed is used at the beginning of maintenance, then will be replaced with independent feed for cost efficiency. Research at P2MKP Fish Boster Center shows that a combination of commercial and independent feeds increases the growth of black tilapia better than single use. This combination can also optimize resources, reduce dependence on commercial feeds, and be an alternative for farmers in increasing the productivity of black tilapia cultivation.